Generativity in older age and its relationship with well-being: Who contributes most is who benefits most? - Villar, Feliciano; López, Olatz; Celdrán, Montserrat (Anales de Psicología / Annals of Psychology, 2013)
The study was aimed both at adapting the McAdams’s generative concern and generative behavior scales into Spanish and at studying generativity in older age and its relationship with well-being. The sample was made up of 165 volunteers aged 65 and over. As well as the Spanish version of the generativity scales, they completed a satisfaction with life scale and an orientation to future scales. Results showed that the Spanish generativity scales had an acceptable level of reliability, similar to the original English versions. Whereas generate concern was related to satisfaction with life, generative behaviors did not. However, both scales were related to orientation to future, although such relationships did not appear in a multivariate analysis. Results emphasize the importance both of generativity in older age and of differentiating generative concern and behaviors, since their benefits could be different.